Effectiveness of an Alcohol-Based Nasal Antiseptic in Reducing MRSA Bacteremia in an Adult Intensive Care Population. (October 2020) - Reeves, Lauren; Barton, Lisa; Nash, Michelle; Williams, Jennifer; Guimera, Don; Simmons, Bryan; Hysmith, Nicholas; Morton, Jackie
Abstract : Background: Hospitalized patients are at an increased risk of invasive infection with Staphylococcus aureus when colonized with the bacteria on admission. Rates of methicillin-resistant Staphylococcus aureus (MRSA) bacteremia are directly correlated with overall patient acuity, placing patients in intensive care areas at greatest risk. Universal decolonization with nasal antibiotic ointments has been shown to reduce the incidence of invasive MRSA in critically ill patients; however, debate remains regarding the long-term efficacy of this strategy and the possibility of developing antimicrobial resistance. An alcohol-based nasal antimicrobial may be an effective alternative. This study evaluated the effectiveness of a twice daily alcohol-based product in reducing the rate of MRSA bacteremia in an academic tertiary-care adult intensive care setting. Methods: Our study was an observational design with retrospective and prospective cohorts each consisting of 61 critical care beds. The baseline incidence of MRSA bacteremia was determined from a 7-month period preceding the implementation of the nasal antimicrobial. At implementation, each admission received an electronic order for an alcohol-based nasal antiseptic that was applied twice daily during the intensive care stay. The primary outcome was the incidence of MRSA bacteremia in each group. MRSA bacteremia was defined by the CDC NHSN criteria after review by an infection prevention nurse. The 2 test was used to compare the rates between the 2 groups, and P < .005 was considered significant. Results: The study periods contained similar patient days, with 12, 475 in the retrospective group and 12, 733 in the prospective group. The rate of MRSA bacteremia in the retrospective cohort was 0.2404 compared to 0 in the prospective cohort. This rate change was statistically significant, with P < .0001. Conclusions: The alcohol-based nasal antiseptic was effective in reducing healthcare-onset MRSA bacteremia in this intensive care population. This approach may be a safe and effective alternative to nasal antibiotic ointment that avoids antibiotic resistance risks. Funding: None Disclosures: None